Review Article: Analysis Caffeine in Powder Coffee Using Spectrophotometry UV-VIS Method - Abriyani, Ermi; Nusaiba Amara, Aisha; Wulandari, Amalia; Setiawati, Devi (Jurnal KESANS : Kesehatan dan Sains, 2022)
Introduction: Caffeine is made by extraction from roasted and ground coffee by dichloromethane after being heated in deionized water mixed with magnesium oxide. The extract was purified, dried and bottled in a bottle of dark glass. A stratified random selection was applied to select a number of vials for the study of homogeneity and stability, which revealed that the prepared reference material was homogeneous and fairly stable.  Objective: This study aims to determine the level of caffeine levels in ground coffee.  The quantification of the % purity of caffeine was performed using a calibrated UV/visible UV/visible spectrophotometer and high-performance liquid chromatography calibrated by the diode-array detection method. Method: This study uses literature review, from several articles published in literature through PubMed, Science Direct,  Researchgate, publons and Google Scholar with articles published from 2012 to 2022.  Result and Discussion: The results obtained from both methods combined to drive the certified value and uncertainty regarding the certified value of the purity of the reference material were found to be 99.86% and the associated uncertainty was ±0.65%, which makes the candidate reference material a very useful calibran in the chemical analysis of food and medicine.  Conclusion: It can be concluded that the caffeine levels contained in robusta and arabica coffee beans with varying soaking duration of 3 days, 5 days, and 7 days there are differences in caffeine levels